Fortifying the Internet of Things: A Comprehensive Security Review - Oroos Arshi,; Aryan Chaudhary, (EAI Endorsed Transactions on Internet of Things, 2023)
A variety of new technologies and their related capabilities have entered daily life in the long run of the IoT technology. Various industrial sectors, including healthcare, facility management, agriculture, energy, and transportation, use IoT technologies.  Interconnected networks are starting to include IoT devices like wearables, commercial appliances, connected electronics, smart grids, smart automobiles, etc. These gadgets produce enormous amounts of data, which are gathered, examined, recorded, and kept on the networks. IoT security is challenging to secure since the devices employ basic processors and operating systems that may not be compatible with advanced security measures. The information and the devices that are used by organizations as a part of their network must be protected against hackers. In this paper, we discuss about overall review of IoT systems that contains the scope of IoT in the  future era, Some of the characteristics of IoT systems, layers including the working Architecture of IoT. We will also discuss some of the vulnerabilities and surface area attacks, application areas regarding IoT. Potential weaknesses in the IoT system could cause serious issues for enterprises. The majority of Internet of Things (IoT) devices have security flaws, including incorrect physical security systems, lack of lock-out mechanisms, weak encryption schemes, improper key management systems, and improper authentication mechanisms, or the use of default credentials. As in the evolving era, security issues are becoming a major problem so some of the security threats of IoT are also mentioned here. This paper also provides the methods for addressing the vulnerabilities to IoT systems' security.
Keywords: IoT security; Lock-out mechanism; Internet-of-Things (IoT); Security threats; Intrustion detection system; graph neural networks